2009
DOI: 10.1080/07448480903221285
|View full text |Cite
|
Sign up to set email alerts
|

Enforcing an Outdoor Smoking Ban on a College Campus: Effects of a Multicomponent Approach

Abstract: Enforcing an outdoor smoking ban using a multiple component package increased compliance with the nonsmoking policy on a college campus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 21 publications
2
64
0
Order By: Relevance
“…Enclosed space rules defined for restaurants may not apply 39 40. Unlike doorways,41 perimeters around non-smoking coworkers would be a moving target and even more difficult to enforce. It was unclear to these workers what stage of completion marked when a building under construction became an indoor workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Enclosed space rules defined for restaurants may not apply 39 40. Unlike doorways,41 perimeters around non-smoking coworkers would be a moving target and even more difficult to enforce. It was unclear to these workers what stage of completion marked when a building under construction became an indoor workplace.…”
Section: Discussionmentioning
confidence: 99%
“…Both policy violator observation and cigarette butt data have been used to collect objective compliance data. 15,16,19,21-23,27 …”
Section: Methodsmentioning
confidence: 99%
“…2 Yet among campuses that have implemented smoke- and tobacco-free policies, perceived lack of enforcement is frequently reported. 3,10,15 Even when there is visible signage, 10 there may be a disregard for the policy, particularly when a plan for compliance is lacking. Student tobacco users expressed they were initially prepared to comply with smoke- or tobacco-free campus policies, but witnessing others disregard the policy without consequence altered their attitudes toward the policy and subsequent noncompliance.…”
Section: Introductionmentioning
confidence: 99%
“…Introducing new legislation ought to be supported by additional intervention programs which would encourage and support the smokers in complying with new regulations and limit the number of smoked cigarettes or eventually quit the smoking habit. Studies by Harrius et al showed that intervention programs that encourage to comply with the smoking ban significantly increase the percentage of people abiding the law [31]. The present study, carried out in Poland among students who began their studies after the amendment was introduced on November 15, 2010, was done after 1 month and after 1 year of introducing the more rigorous antinicotine regulations.…”
Section: Complying With Smoking Ban After Intervention O R I G I N a mentioning
confidence: 99%